(untitled) (Bodhi Path, 2021)
After attaining the perfect and complete enlightenment, Ṡākyamuni Buddha, the Embodiment of Wisdom and Compassion, turned three Wheels of Doctrine at different places in India. The first Wheel of Dharma of the four noble truths was turned at Sarnath, Varanasi which was mainly prescribed for those of Ṡrāvaka family; the second Wheel of Dharma of signlessness was turned at Gṛdrakūṭa near Rājgir which was mainly prescribed for those of sharp-minded Mahāyāna family; and the third Wheel of Dharma of Good Discrimination was turned at Vaishali etc., which was also prescribed for the Mahāyāna family. Not only this, having appeared in the form of Vajradhara, the Complete Enjoyment Body of the Buddha, he also turned the Wheel of Tantra at Ṡrī Dhānyakūṭa at the request of King Chandragarbha for the disciples who are especially inclined towards the profound, i.e., the disciples of superior intelligence. Among the three Wheels of Doctrine, the Teacher spoke on Prajñāpāramitāsūtra (Wyl. shes rab kyi pha rol tu phyin pa’i mdo; Eng. Perfection of Wisdom Sūtra) in the middle Wheel of Doctrine. There are several Prajñāpāramitāsūtra of varying lengths. The most extensive of these is the Ṡatasāhasrikāprajñāpāramitāsūtra (One Hundred Thousand-Stanza Perfection of Wisdom Sūtra) which in the Tibetan translation occupies twelve volumes. There is also a medium length sūtra of twenty-five thousand stanzas in three volumes and a short and single-volume sūtra in eight thousand stanzas. In addition there is an even shorter sūtra in eight chapters of verse known as the Condensed Perfection of Wisdom Sūtra (Skt. Prajñāpāramitāsañcayagāthā) too. On the other hand, terminologically it is divided into four: Natural (Real) Prajñāpāramitā, Prajñāpāramitā in scriptural form, Prajñāpāramitā of Path and Resultant Prajñāpāramitā Among them, the second one has seventeen1 types in total.